Antimicrobial Investigation and Structural Study of 4′‐Methylazobenzene‐2‐sulfenyl Thiocyanate by X‐Ray Diffraction, DFT, and Ab Initio HF Calculations. Issue 6 (25th October 2013) - Bhattacharjee, Tirtha; Barman, Pranjit; Thakuria, Tapan; Sarma, Rupam; Dutta Kalita, Ranjan; Sarma, Bipul
ABSTRACT 4′‐Methylazobenzene‐2‐sulfenyl thio‐cyanate (MABS‐SCN) was synthesized in an aqueous medium and characterized by 1H nuclear magnetic resonance, Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, and elemental analysis. The crystal structure was confirmed by single crystal X‐ray diffraction and its geometry was optimized in ground state by Hartree–Fock model and (B3LYP) density functional theory, and in solution (ethanol) using polarized continuum model at restricted HF using the basis set 6–31+G*. The compound crystallizes in orthorhombic space group Pbca, with unit cell parameters a = 7.165 (7) Å, b = 18.846 (2) Å, c = 20.379 (2) Å, V = 2752.1 (5) Å3, and Z = 8. It attains a planar thiadiazolium salt structure due to strong ortho azo–sulfur interaction imparting exceptional thermal stability, nonreactive solubility in aqueous medium, and high melting crystalline solid nature. A weak intramolecular CH…S type interaction, one CH…S type, four CH…N type intermolecular hydrogen bonds, and van der Waal's interactions are believed to be the stabilizing force for the crystal structure. MABS‐SCN was also tested for antimicrobial activity.